Development and validation of an interview guide for examining the effects of sports careers on the quality of life of retired Portuguese football players - Teixeira, E.; Silva, C.; Vicente, A. (Frontiers in Psychology, 2024)
Introduction: Considering the importance of assessing the impacts resulting from a sport career, this study aimed at developing and validating a semi-structure interview guide suitable for quantifying the sociodemographic and epidemiological profile of former professional football players.